Model based optimization of the control strategy of a gasifier coupled with a spark ignition engine in a biomass powered cogeneration system. (September 2019) - Costa, M.; Rocco, V.; Caputo, C.; Cirillo, D.; Di Blasio, G.; La Villetta, M.; Martoriello, G.; Tuccillo, R.
Highlights: A numerical model of real combined heat and power plant of the micro scale of power fueled by wood chip is presented. The model simulate the gasification process to obtain the syngas and its combustion in an Internal Combustion Engine. The validation is made as based on a specific experimental campaign. An algorithm of optimization is used to find the optimal working parameters to improve the electric efficiency. It is possible to obtain an improvement of 6% on electric power. Abstract: Model-based optimization offers the appealing opportunity of interpolating performance of a physical system between settings and of inferring its behaviour from previously unobserved areas of the parameter space, up to the optimal one. Application of this technique to micro-Combined Heat and Power (m-CHP) generation based on biomass gasification allows better exploiting the potential of this renewable energy source (RES) and of the specific technology for thermo-chemical conversion. A numerical model of a real CHP plant of the micro-scale of power, the ECO20 manufactured by the Italian Company Costruzioni Motori Diesel S.p.A., is presented in this paper as coupled with an optimization algorithm for the search of the best performance in terms of electric power output. The considered m-CHP system, made of a gasifier, a syngas cleaning system and a spark ignition Internal Combustion Engine (ICE) working as a co-generator, is fueled by woodchip. The plant model is realized by schematizing the whole biomass-to-energy chain within the Thermoflex™ environment and, simultaneously, by improving the prediction of the ICE performance through a properly developed and validated one-dimensional (1D) model in GT-Suite®. Simulation of the combustion process is specifically customized for syngas use, namely to account for the extreme variability of this fuel that strongly depends upon the kind of processed biomass and the gasifier operating conditions. The system model is validated on the ground of experimental data collected on the real plant and is coupled with the modeFRONTIER™ software for the optimal choice of the main operating parameters. The final purpose of the work is the assessment of a framework for the energetic and environmental optimization of biomass-powered cogeneration systems suitable of being used under various conditions and for various purposes. The here reported case study consists of the optimization of the electric power output by the considered m-CHP unit as a function of the equivalence ratio at the gasifier and of the ICE spark advance. Starting from an electric output of 17 kW, measured during the experimental campaign, it is demonstrated that an improvement of 6% on the electric power can be reached by acting only on the system parameters settings, without changing the system components.